Automated Blood Pressure Control with Closed Loop System - Dubauskiene, N.; Markevicius, V.; Valinevicius, A.; Navikas, D. (Elektronika ir Elektrotechnika, 2012)
Typical risk reduction measures are not sufficient to reduce the probability of errors resulting from operator mistakes. Improvement of the device software and hardware, adding more alerts and alarms is not enough to significantly reduce the risk of such type of hazards, so there is a need of new methods to improve the safety of medical devices. One of possible solutions – systems with closed loop control. Integrating patient monitoring and drug infusion devices in to integrated system and using a controller, which would be able to asses required changes in the infusion according to patients vital signs might make it possible to reduce the probability of hazards arising from the need of constant monitoring, overdose and lack of appropriate timely reaction when a problem occurs. Modelling of closed loop systems show that the objectives, such as constant blood pressure in post-operative patients, can be achieved. Mathematical modelling is not sufficient to evaluate all the environmental factors, but it is helpful to decide the complexity of the system needed in each case. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2802